Experience in treating disseminated breast cancer after multimodality therapy - G. A. Khakimov; N. R. Shayusupov; G. F. Miryusupova (Опухоли женской репродуктивной системы)
Median survival in patients with disseminated breast cancer (BC) is less than 3 years; moreover, 25-30 and 10% survive > 5 and > 10 years, respectively. Current systemic therapy increases median survival rates by only 3-4 months as compared with patients who do not receive this therapy. The data given in the paper are based on the analysis of a follow-up of 36 women aged 30 to 57 years who had BC dissemination 2 years after multimodality treatment in the Tashkent City Cancer Dispensary in the period 2006 to 2008. Despite the fact that the current multidrug therapy regiments were used, there were no dramatic changes in survival rates. However, the attain- ment of stabilization and regression of metastatic foci in this category of patients allows clinicians, oncologists, and their patients to hope to control this disease.